2019
DOI: 10.1002/jez.2326
|View full text |Cite
|
Sign up to set email alerts
|

Effects of temperature and meal size on the postprandial metabolic response of Leptodactylus latrans (Anura, Leptodactylidae)

Abstract: The postprandial increment of metabolism, often referred to as specific dynamic action (SDA), encompasses the summed costs of meal ingestion, digestion, absorption, and assimilation. Different SDA parameters, such as its magnitude, duration, and relative cost, are affected by a diverse set of environmental and physiological determinants, including meal size and body temperature. While the influence of these variables has been thoroughly examined in most ectothermic vertebrate groups, few studies have focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 77 publications
0
11
1
1
Order By: Relevance
“…Neotropical frog (Timpone et al, 2019)). Despite the higher cost of digestion (SDA) at 30°C, C. newmannii larvae also showed a higher aerobic scope (AS) at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…Neotropical frog (Timpone et al, 2019)). Despite the higher cost of digestion (SDA) at 30°C, C. newmannii larvae also showed a higher aerobic scope (AS) at 30°C.…”
Section: Discussionmentioning
confidence: 99%
“…A pesar de las adaptaciones desarrolladas para tolerar los cambios en la temperatura, se describió que diferentes especies tienen una selectividad térmica para potenciar el retorno energético, mientras que al realizar los procesos de ingestión del alimento, digestión, absorción y asimilación por encima de estas preferencias el proceso ocurre más rápido, pero con un menor rendimiento energético, como se estudió en Leptodactylus latrans (Timpone, Gavira & Andrade, 2019)…”
Section: Efectos De La Temperatura En Anuros Y Su Relación Con La Glucosaunclassified
“…Previous studies on SDA in amphibians have found that meal size has a significant effect on SDA (Secor & Faulkner 2002, Secor & Boehm 2006, Secor et al 2007, Timpone et al 2020. Ingesting prey of different sizes requires adjustments to the physiological processes underlying meal digestion, such as gut evacuation, and has important ecological and energetic implications (Secor & Faulkner 2002, França et al 2004, Timpone et al 2020. The SDA duration and en ergy expended on SDA in amphibians, like other ecto thermic animals, usually increase with increasing meal size (Secor & Boehm 2006, Secor et al 2007).…”
Section: Introductionmentioning
confidence: 98%
“…Intraspecific variations in SDA responses are at tri buted to differences in meal characteristics and envi-ronmental conditions (Secor et al 2007). Previous studies on SDA in amphibians have found that meal size has a significant effect on SDA (Secor & Faulkner 2002, Secor & Boehm 2006, Secor et al 2007, Timpone et al 2020. Ingesting prey of different sizes requires adjustments to the physiological processes underlying meal digestion, such as gut evacuation, and has important ecological and energetic implications (Secor & Faulkner 2002, França et al 2004, Timpone et al 2020.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation